STRATEGI PENGEMBANGAN USAHA LEBAH MADU KELOMPOK TANI SETIA JAYA DI DESA RAMBAH JAYA KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU - Andri Setiawan (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2017)
Honey bee breeding business is a business development and sales of livestock products of honey bees. Development of beekeeping businesses have good prospects for the future, the need for business development strategies to increase public interest in promoting the beekeeping business. The business location of honeybees of Farmers Group Setia Jaya located in the village Rambah Jaya subdistrict Bangun Purba, district Rokan Hulu has good prospects to produce the amount of honey due to its location adjacent to the acacia plantations owned by the Company Sumatra Silvia Lestari and rubber plantations has planted by local people. It is obviously very profitable for farmers honeybees as a source of food or feed bees directly derived from nature. This study aims to find out what activities undertaken farmer groups to develop a business honeybees. So that this business can be continue to survive and evolve in order to meet growing consumer demand. The research was conducted in February until March 2015. Based on the results of the research shows that the first Setia Jaya Farmer's Group in conducting maintenance and upkeep, harvesting, packaging and distribution (marketing) is still done manually, which means the traditional and still wearing human intervention so that the results are not optimal. Second Alternative business development strategies that can be applied by Farmers Group Setia Jaya, one of which is making honey product quality, create excellent honey products and maintain the authenticity and purity of the honey as well as improving the productivity of honey in order to increase customer loyalty to the farmer groups